Desenvolvimento de um gel contendo troxerrutina e aplicação com atividade antioxidante e anti-inflamatória em modelo de periodontite em camundongos - Dias, André Tavares de Freitas Figueiredo (2024)
Periodontitis is a disease characterized by chronic inflammation. Its main cause is infectious in nature, affecting the tissues that support the teeth. This condition may play a role in the development of various pathological conditions, as the bacteria associated with its development release inflammatory substances and toxins, which enter the bloodstream, potentially triggering systemic inflammation. Natural products, such as troxerutin derived from rutin, have been the subject of study due to their antioxidant and anti-inflammatory properties, as well as their facilitation of bone repair. This study aimed to investigate, for the first time, the action of a gel containing troxerutin in the treatment of experimental periodontitis, exploring the possible associated mechanisms. Periodontitis was induced in 48 previously anesthetized mice by placing a cotton suture thread around the first lower molars. The animals were divided into five groups: a control group without disease induction (naive), a control group with periodontitis receiving local application of a gel containing only the dilution vehicle (HPMC), and three groups receiving local application of the gel containing different concentrations of troxerutin (0.1%, 0.5%, and 1%) after suture placement, once daily for 11 days. Euthanasia occurred on the 11th day, and the mandibles were collected for histopathological analyses, osteoclast counting, and morphometric studies of bone loss. Additionally, bone alkaline phosphatase assay was performed on blood collected on the 11th day, and RANKL and OPG analysis was conducted by western blotting. Gingival tissues were dissected and immediately frozen until assays were performed to verify the concentrations of oxidative stress markers (indirect evaluation of NO by nitrite/nitrate, reduced glutathione - GSH-, and malondialdehyde -MDA-). Animals treated with troxerutin-containing gels showed a significant decrease in inflammatory infiltrate in periodontal tissues, accompanied by a lower count of active osteoclasts compared to the HPMC group. This result was associated with a lower alveolar bone loss index, corroborating with higher OPG expression and lower RANKL expression in the troxerutin-treated groups (0.5% and 1%) compared to the HPMC group. Furthermore, statistical differences were observed in alkaline phosphatase levels in the troxerutin-treated groups (0.5% and 1%) compared to the HPMC group. Other results obtained through GSH, MDA, and NO dosage show greater preservation of GSH and lower concentrations of MDA and NO in the groups treated with troxerutin (0.5% and 1%), highlighting its anti-inflammatory and antioxidant properties, indicating the therapeutic potential of troxerutin, at the tested concentrations, in experimental periodontitis.